Public Private Partnership in Providing Affordable and Gap Housing in Inner-City Areas: City of Cape Town Case Study - Uwoyashatse, Eric (Department of Construction Economics and Management, 2024)
Developers in South Africa are confronted with several constraints in supplying affordable housing to low-income earners and this includes the non-availability of land, end-user un-affordability, poor planning, and limited partnerships between public and private sector role players. Apartheid and its' associated spatial planning served to locate and exclude the poor in dormitory townships far away from centres of economic, employment and major income opportunities. Consequently, social inequalities have increased dramatically between the South African population along racial lines. Furthermore, South Africa's inner cities lack systematic and comprehensive affordable housing developments, incentivised by the state and capable of attracting private investors. This study explores measures capable of enhancing and restructuring affordable housing development in inner-city areas, with Cape Town as case study. For the purpose of this research, the affordable housing market is defined as those households with incomes which are too high to receive freegovernment subsidised houses, but too low to afford even the cheapest option on the market and is also referred to as the ‘gap' market. This research was conducted with the aim to determine what can be done through partnerships between the private and public sectors to stimulate the investment and development of well-located and affordable housing. Therefore, this research is solution-based, focusing on ways to address challenges and maximise policy, financial, structural instruments and other mechanism that exist within the affordable housing sector. The findings indicated that the use of public-private-partnerships in South Africa in affordable housing delivery is still in its incipient stage. Therefore, it is advisable to learn from international experiences where public-private-partnerships are used to provide affordable housing. The study identified various constraints on providing housing through public-private-partnerships, as well as possible enablers, investment, and incentive strategies. Recommendations made, including legal, regulatory, and finance mechanisms that can assist policymakers in paving the way for successful PPP implementation. The findings highlighted the most frequently used, suitable and recommended types and forms of publicprivate-partnerships in housing delivery.